Do Primary Schools Have Contextual Influence on Health Behavior? A Multilevel Evidence from Nganjuk, East Java - Frida Indriani; Pawito Pawito; Eti Poncorini Pamungkasari (Journal of Health Promotion and Behavior, 2019)
Background: Health problems among primary school age children caused by poor personal hygiene can be prevented by good clean and healthy life behavior. Clean and healthy life behavior is affected by perceived susceptibility, perceived seriousness, perceived benefit, perceived barrier, cues to action, and self-efficacy. This study aimed to analyze the contextual effect of primary school on clean and healthy life behavior in primary school age children in Nganjuk, East Java.Subjects and Method: This was cross sectional study conducted at 25 primary schools in Nganjuk, East Java, from August to December 2019. There were 200 primary school  age children aged 6-12 years involved as the sample of this study. The study used stratified random sampling. The dependent variable was clean and healthy life behavior. The independent variables were perceived susceptibility, perceived seriousness, perceived benefit, perceived barrier, cues to action, and self-efficacy. This study used questionnaires to collect the data. This study used multilevel multiple logistic regression with Stata 13 to analyze the data.Results: Clean and healthy life behavior in the primary school age children increased with high perceived susceptibility (b=1.06; 95%CI=0.31 to 1.80; p=0.005), high perceived seriousness (b= 0.92; 95%CI=0.16 to 1.68; p=0.018 ), strong perceived benefit (b=0.76; 95%CI=0.05 to 1.47; p= 0.036), strong cues to action (b=0.97; 95%CI=0.26 to 1.68; p=0.007), and strong self-efficacy (b= 1.16; 95%CI=0.43 to 1.89; p=0.002). Clean and healthy life behavior in the primary school  age children decreased with strong perceived barrier, but the result was statistically non-significant (b= -0.27; 95%CI=-1.02 to 0.33; p=0.484). Primary school had a contextual effect on clean and healthy life behavior (ICC 17.33%).Conclusion: Clean and healthy life behavior in primary school  age children is affected by perceived susceptibility, perceived seriousness, perceived benefit, perceived barrier, cues to action, and self-efficacy. Primary school has a contextual effect on clean and healthy life behavior.Keywords: clean and healthy life behavior, Health Belief Model, contextual of primary schoolCorrespondence:Frida Indriani, Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir.Sutami 36A, Surakarta, Central Java, Indonesia. Email: nersfrida15@gmail.com. Mobile: 082226327646Journal of Health Promotion and Behavior (2019), 4(3): 235-245https://doi.org/10.26911/thejhpb.2019.04.03.08